Equivalence in measurement - Schriesheim, Chester; Neider, Linda L., 1953- (Research in management ;, 2001)
This volume highlights research and conceptual insights into one of the most basic, and yet, perplexing research issues in management-handling and assessing the comparability of our measurement devices across groups and measures. One of the most consistently difficult concerns in management research over the past three decades has been trying to reconcile measurement equivalence issues utilizing diverse samples. Given the emphasis on diversity in the human resources area and the internationalization of business and management, measurement equivalence is more of a general concern now than ever before. If we are not able to successfully address concerns about measurement equivalence, research examining differences between groups could be highly misleading and/or erroneous. Consequently, we hope that the thoughtful contributions of the scholars in this volume will help future scholars to better address measurement equivalence concerns.